Characteristics and conditions for ignition of bio-coal mixtures based on coal and forest combustible material. Issue 5 (October 2020) - Syrodoy, S.V.; Kuznetsov, G.V.; Gutareva, N.Y.; Kostoreva, Zh.A; Kostoreva, A.A.; Nigay, N.A.
Abstract: The results of the experimental studies of the ignition process of a pulverized fuel mixture based on coal and biomass — forest combustible material (FCM) have been given. As the second component of the fuel the wastes of various deciduous or coniferous species of trees have been used. The experiments have been carried out on the equipment that provides a fairly low level of error when registering the main characteristics (ignition delay time of the fuel particles tign, ambient temperature Tg ) of heat and mass transfer processes occurring together during ignition of bio-coal fuel during thermal preparation. It has been established that the addition of biomass to coal leads to a significant reduction (up to 30%) of the entire ignition period of the fuel mixture. The video recording of the ignition processes has allowed to identify the main stages of thermal preparation and ignition of the bio-coal fuel particles. It has been established that the particles of biomass (leaf or fir needles) ignite faster than coal. A mathematical model has been developed based on the results of a detailed analysis of the videograms of the ignition process of the bio-coal mixtures describing the joint flow of the main processes of heat and mass transfer under conditions of the intense phase and thermochemical transformations. A numerical simulation of the ignition process has been carried out and the ignition delay times have been established. A comparative analysis of the theoretical and experimental values of tign has shown their good conformance. Highlights: The processes of ignition of bio-coal mixtures based on coal and wood combustible material have been experimentally studied. Adding forest waste to coal significantly shortens the ignition period. Developed a mathematical model of the process of ignition of particles of bio-coal fuel. Moist forest fuel significantly affects the rate of ignition of a bio-coal mixture.